Recognition and democratisation: New roles for traditional leaders in Sub-Saharan Africa - Helene Maria Kyed; Lars Buur (Danish Institute for International Studies (DIIS), 2006)
Against the background of the European Conference on African Studies (AEGIS), held in London from 30 June to 2 July 2005, where the authors hosted two panels on the `New roles for traditional leaders in tax collection and rural development: expectations, obstacles and conflicts', this paper outlines and discusses the main points that emerged from a selection of the papers presented at the sessions. The present working paper reviews recent literature on the role of traditional leaders in Sub-Saharan Africa and discusses the potential, often complex consequences of the current waves of democratisation and recognition of traditional leaders in decentralised governance. Despite the ambiguous relationship between traditional leaders and post-colonial states that has characterised Sub-Saharan Africa since the achievement of independence, traditional leaders have been drawn into mainstream processes of state-building and democratisation in various ways. Traditional leaders now officially form part of establishing some kind of bottom-up benign governance based on a variety of different local, national and transnational modalities of power. Although many instances of the state recognition of traditional leaders have been made in the name of democratisation, the contributions to the panels at the London conference question whether recognition in fact implies a serious challenge to the kind of state centralism and/or authoritarianism that have characterised many post-colonial African states. The working paper thus argues for the need to scrutinize official recognition from an empirical perspective and ask how in practice traditional leaders are drawn into local governance through state policies. An edited version of this working paper and the papers it refers to from the European Conference on African Studies will appear in an edited book or special issue of an international journal. An appendix with the selected paper titles and abstracts are included at the end of this paper.
Keywords: 330; Politiker; Politischer Wandel; Dezentralisierung; Zentralafrika; Demokratisierung